KONSEP AQSAM (SUMPAH), AMTSAL (PERUMPAMAAN), DAN QISHASH (CERITA) DALAM AL-QUR’AN - Ahmad Munirul Hakim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This article examines three fundamental aspects of the miraculous nature of the Qur’an’s style and content, namely Aqsam (oaths), Amtsal (parables) and Qishash (stories). These three elements constitute an important discourse within the study of Ulumul Qur’an, serving to convey divine messages effectively to humankind. This paper aims to describe, classify, and analyse the significance of each of these concepts in a holistic and comprehensive manner. This article employs a library research method using a content analysis approach. Data was collected through documentation techniques from various relevant literature, then examined and classified based on etymological and terminological meanings, categorisation by type, along with examples of verses. The findings of the study present three main conclusions regarding the miraculous nature of the Qur’an. Firstly, the concept of Aqsam (Oaths) serves to affirm and reinforce the truth of information in order to convince people. Secondly, the concept of Amtsal (Parables) is classified into musharrahah (explicit), kanimah (implicit), and mursalah (detached). These are further divided into good parables (the attributes of Allah, Paradise) and bad parables (the character of hypocrites, worldly life). Thirdly, the concept of Qishash (Narratives) contains accounts of the Prophets, previous communities, and events during the time of the Prophet Muhammad (peace be upon him).